Predicting mortality and safe discharge in drowning victims: A comprehensive analysis of neurological and clinical outcomes in the emergency department - Süleyman Gökhan Kara; Başak Bayram; Şebnem Şakar Halaç; Osman Sönmez; Neşe Çolak (Turkish Journal of Emergency Medicine, 2025)
OBJECTIVES: This study sought to identify risk factors linked to mortality, intensive care unit admission, and poor neurological outcomes among drowning victims and to find markers for safe discharge from the emergency department (ED). METHODS: This retrospective cross-sectional study evaluated all drowning victims presenting to both adult and pediatric EDs at a single center over an 11-year period. Variables such as arrival time at ED, age, type of water, comorbid diseases, vital signs, treatments given, and prehospital interventions were assessed. RESULTS: The study found that early basic life support (BLS) by bystanders significantly improves survival and neurological outcomes. Respiratory rate, oxygen saturation, and Glasgow Coma Scale (GCS) were identified as independent risk factors for poor clinical outcomes. While the Szpilman clinical score is useful, it alone is not sufficient for predicting poor clinical outcomes. CONCLUSIONS: For optimal management of drowning victims, immediate BLS is crucial. In the ED, respiratory rate, oxygen saturation, and GCS should be closely monitored. Drowning victims with a GCS of 15, normal respiratory rate, normal oxygen saturation, and Szpilman score below 3 can be safely discharged from the ED.